Recommendations for services for people living with chronic breathlessness in advanced disease: Results of a transparent expert consultation. (27th December 2018) - Brighton, Lisa Jane; Tunnard, India; Farquhar, Morag; Booth, Sara; Miller, Sophie; Yi, Deokhee; Gao, Wei; Bajwah, Sabrina; Man, William DC; Reilly, Charles C; Ogden, Margaret; Bailey, Sylvia; et al.
Chronic breathlessness is highly distressing for people with advanced disease and their informal carers, yet health services for this group remain highly heterogeneous. We aimed to generate evidence-based stakeholder-endorsed recommendations for practice, policy and research concerning services for people with advanced disease and chronic breathlessness. We used transparent expert consultation, comprising modified nominal group technique during a stakeholder workshop, and an online consensus survey. Stakeholders, representing multiple specialities and professions, and patient/carers were invited to participate. Thirty-seven participants attended the stakeholder workshop and generated 34 separate recommendations, rated by 74 online survey respondents. Seven recommendations had strong agreement and high levels of consensus. Stakeholders agreed services should be person-centred and flexible, should cut across multiple disciplines and providers and should prioritize breathlessness management in its own right. They advocated for wide geographical coverage and access to expert care, supported through skills-sharing among professionals. They also recommended recognition of informal carers and their role by clinicians and policymakers. Overall, stakeholders' recommendations reflect the need for improved access to person-centred, multi-professional care and support for carers to provide or access breathlessness management interventions. Future research should test the optimal models of care and educational strategies to meet these recommendations.